Plasmodium knowlesi infecting humans in Southeast Asia: What’s next? - Jeyaprakasam, Nantha Kumar; Liew, Jonathan Wee Kent; Low, Van Lun; Wan-Sulaiman, Wan-Yusoff; Vythilingam, Indra (PLOS Neglected Tropical Diseases, 2021)
Plasmodium knowlesi, a simian malaria parasite, has been in the limelight since a large focus of human P. knowlesi infection was reported from Sarawak (Malaysian Borneo) in 2004. Although this infection is transmitted across Southeast Asia, the largest number of cases has been reported from Malaysia. The increasing number of knowlesi malaria cases has been attributed to the use of molecular tools for detection, but environmental changes including deforestation likely play a major role by increasing human exposure to vector mosquitoes, which coexist with the macaque host. In addition, with the reduction in human malaria transmission in Southeast Asia, it is possible that human populations are at a greater risk of P. knowlesi infection due to diminishing cross-species immunity. Furthermore, the possibility of increasing exposure of humans to other simian Plasmodium parasites such as Plasmodium cynomolgi and Plasmodium inui should not be ignored. We here review the current status of these parasites in humans, macaques, and mosquitoes to support necessary reorientation of malaria control and elimination in the affected areas.